PENGARUH KESENJANGAN SOSIAL TERHADAP MINAT BELAJAR SISWA DI MI DARUSSALAM SIDOARJO - marsanda (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2023)
This research aims to explore the influence of social disparity on students' learning interest in MI Darussalam Sidoarjo. Social disparity can create inequality in access and learning opportunities among individuals, which in turn can affect students' learning interest. This research used a quantitative approach with a questionnaire as the data collection tool. The research sample consisted of 15 randomly selected students from MI Darussalam Sidoarjo. The results of this study indicate a significant relationship between social disparity and students' learning interest. Students who experience social disparity tend to have low learning interest, while students who do not experience social disparity tend to have high learning interest. These findings have important implications for the development of learning strategies that can help reduce social disparity and enhance students' learning interest in MI Darussalam Sidoarjo. Keywords: disparity, social, interest.